Controlled transportation of droplets and higher fog collection efficiency on a multi-scale and multi-gradient copper wire. Issue 47 (7th June 2017) - Xing, Yan; Wang, Sijie; Feng, Shile; Shang, Weifeng; Deng, Siyan; Wang, Lei; Hou, Yongping; Zheng, Yongmei
Abstract : Via a one-step gradient anodic oxidation, copper wire with a multi-scale structure and a multi-gradient was fabricated and controlled self-propelling of droplet was achieved. Abstract : Via a one-step gradient anodic oxidation, a copper wire with a multi-scale structure and multi-gradient was successfully fabricated, which could realize self-propulsion of droplets and with a well-controlled transport distance. Compared to the previous study, herein, the wire exhibited not only a longer transport distance of the droplet, but also a much higher water collection efficiency.